2014
DOI: 10.1016/j.vetmic.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virulent and attenuated transmissible gastroenteritis virus on the ability of porcine dendritic cells to sample and present antigen

Abstract: Virulent transmissible gastroenteritis virus (TGEV) results in an acute, severe pathology and high mortality in piglets, while attenuated TGEV only causes moderate clinical reactions. Dendritic cells (DCs), through uptake and presentation of antigens to T cells, initiate distinct immune responses to different infections. In this study, an attenuated TGEV (STC3) and a virulent TGEV (SHXB) were used to determine whether porcine DCs play an important role in pathogenetic differences between these two TGEVs. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…The ability of promoting DC function for cellular maturation, induce lymphocyte cell proliferation, pro-inflammatory cytokine secretion, and antigen presentation is necessary to assess the potential of antigen initiation for both innate and adaptive immune responses [22][23][24][25]. We demonstrated that the Zhejiang08 strain was a stronger and more potent inducer of DC maturation and mRNA expression of IL-12 and IFN-c in DCs than CV777.…”
Section: Discussionmentioning
confidence: 90%
“…The ability of promoting DC function for cellular maturation, induce lymphocyte cell proliferation, pro-inflammatory cytokine secretion, and antigen presentation is necessary to assess the potential of antigen initiation for both innate and adaptive immune responses [22][23][24][25]. We demonstrated that the Zhejiang08 strain was a stronger and more potent inducer of DC maturation and mRNA expression of IL-12 and IFN-c in DCs than CV777.…”
Section: Discussionmentioning
confidence: 90%
“…The piglets were handled and maintained under strict ethical conditions according to international recommendations for animal welfare. All group piglets were euthanized at 21 days after secondary immunization, and the intestinal segments were collected as previously described but with minor alterations (Zhao et al 2014). In detail, upon washing with ice-cold PBS, the fixed tissues were immediately embedded in OCT (embedding medium for frozen tissue specimens; Sakura, USA) and then stored at − 80°C until further use.…”
Section: Experimental Designmentioning
confidence: 99%
“…Our observation is further supported by the absence of cell death after PEDV exposure. Similarly, conflicting results have been published regarding the susceptibility of Mo-DC to TGEV, a close relative of PEDV (Guzylack-Piriou et al, 2006;Zhao et al, 2014). Further research is needed to determine the underlying reasons for the discrepancy results.…”
Section: Discussionmentioning
confidence: 96%